Clinical and economic impact of pharmacist interventions in an ambulatory hematology–oncology department. (July 2020) - de Grégori, Jonathan; Pistre, Pauline; Boutet, Meredith; Porcher, Laura; Devaux, Madeline; Pernot, Corinne; L Chrétien, Marie; Rossi, Cédric; Manfredi, Sylvain; Dalac, Sophie; Gueneau, Pauline; Boulin, Mathieu
Objectives: To evaluate clinical and financial impact of pharmacist interventions in an ambulatory adult hematology–oncology department. Methods: All cancer patients receiving a first injectable immuno- and/or chemotherapy regimen were included in this prospective study over a one-year period. The clinical impact of pharmacist interventions made by two clinical pharmacists was rated using the Clinical Economic and Organizational tool. Financial impact was calculated through cost savings and cost avoidance. Main results: Five hundred and fifty-eight patients were included. A total of 1970 pharmacist interventions were performed corresponding to a mean number of 3.5 pharmacist interventions/patient. The clinical impact of pharmacist interventions was classified as negative, null, minor, moderate, major and lethal in 0, 84 (4%), 1353 (68%), 385 (20%), 148 (8%) and 0 cases, respectively. The overall cost savings were €175, 563. One hundred and nine (6%) of all pharmacist interventions concerned immuno- or chemotherapy regimen for cost savings of €148, 032 (84% of the total amount of cost savings). The cost avoidance was €390, 480. Cost avoidance results were robust to sensitivity analyses with cost of preventable adverse drug event as main driver of the model. When the cost of employing a pharmacist was subtracted from the average yearly cost savings plus cost avoidance per pharmacist, this yielded a net benefit of €223, 021. The cost–benefit ratio of the clinical pharmacist was €3.7 for every €1 invested. Principal conclusions: To have two full-time clinical pharmacists in a 55-bed ambulatory adult hematology–oncology department is both clinically and financially beneficial.